2002
DOI: 10.1108/09590550210429522
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of sales promotions in UK supermarkets: a consumer view

Abstract: UK supermarkets need to be able to assess the current efficacy of the budget they allocate to promotional activities aimed at boosting sales. Therefore, the main objective of this article is to investigate consumer response to the four different promotional deals most commonly used in UK supermarkets: coupons, price discounts, samples and “buy‐one‐get‐one‐free”. Multi discriminant analysis was used on a study of 160 respondents to analyse whether there was an association between the four consumer promotional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
116
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 35 publications
11
116
0
9
Order By: Relevance
“…Further consideration of where and when it is and is not appropriate to market less healthy foods to children may be valuable. Price promotion leads to a significant increase in sales (20,21) . The higher proportion of less healthy foods on promotion may steer customers to choose these over any healthier options available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further consideration of where and when it is and is not appropriate to market less healthy foods to children may be valuable. Price promotion leads to a significant increase in sales (20,21) . The higher proportion of less healthy foods on promotion may steer customers to choose these over any healthier options available.…”
Section: Discussionmentioning
confidence: 99%
“…The balance of healthy to less healthy foods displayed at checkouts influences customers' behaviour, with healthy foods being more likely to be selected when they are in the majority (19) . Price promotions are also known to influence purchasing (20,21) and may further contribute to impulse purchases.…”
mentioning
confidence: 99%
“…This assumption is made based on the results of studies such as Lee (2002), who found that sales campaigns focused on savings (monetary promotions) performed better than non-monetary promotions and that monetary promotions are preferred by consumers over non-monetary promotional actions. Gilbert and Jackaria (2002) found that discount promotions (monetary) have a greater influence on purchase decisions than do non-monetary promotions (e.g., prize contests). More recently, Nusair, Yoon, Naipaul and Parsa (2010) similarly found that discount promotions (monetary) were more effective than prize campaigns (non-monetary) when the purpose is to influence service acquisition.…”
Section: Literature Review and Working Hypothesesmentioning
confidence: 99%
“…In the process of making buying decisions in the clearance sales, the purchase acceleration and product trial are found to be the two most infl uential variables related to a discount. 25 Thus, the hypothesis may be framed as…”
Section: H2mentioning
confidence: 99%